CHINESE RENEWABLE INVESTMENTS: THREATS AND OPPORTUNITIES - Alisher Bobonazarov (Journal Park Publishing, 2025)
China’s growing role in global renewable energy investment presents a complex landscape of significant opportunities and persistent threats. This article examines the drivers behind China’s overseas renewable investments, particularly in developing countries, including its industrial competitiveness, supportive financing, and strategic alignment with global climate goals. Concurrently, it analyzes the challenges posed by geopolitical tensions, financial inefficiencies, host-country regulatory barriers, and evolving global economic conditions. The paper, in the end, holds the view that China is in a very good strategic position to be the first mover in the worldwide green energy transition. However, the long-term viability and the extent of her investments depend on her ability to tackle a very complex set of risks both at home and abroad.
Keywords: China, renewable energy investment, geopolitical risk, sustainable finance, energy transition, Belt and Road Initiative, solar power, wind power